Descriptive Study on Kempo Martial Arts and Its Effects on the Students' Mental Resilience in SBS Young Entrepreneur School - Robianti, Febi; Doddy Widodo Laksono; Novi Widiasari; Khalila Amalia Raisya Yamani; Herlin Kusumasari; Maryadi, Ari; Isnan Santoso (Jurnal Pendidikan Non formal, 2024)
This descriptive study explores the impact of Shorinji Kempo martial arts training on the mental resilience of students at SBS Young Entrepreneur School, Bekasi, Indonesia. Over two years, the school integrated Kempo into its curriculum to enhance students' self-discipline, adaptability, and psychological strength—qualities essential for academic, social, and personal success. Kempo, a martial art introduced to Indonesia in the 1960s, combines physical techniques with philosophical teachings that emphasize resilience and personal growth. The study aims to assess how Kempo training contributed to students’ mental resilience, focusing on stress management, emotional regulation, self-confidence, and overall psychological well-being. The research utilized a descriptive design, employing pre- and post-training interviews, questionnaires, and observations to assess students' progress. Findings indicate significant improvements in students' technical knowledge, physical fitness, and mental resilience. As students progressed through the training, they developed greater self-confidence, enhanced discipline, and stronger stress management abilities. The study also observed improvements in teamwork, focus, and adaptability, all of which contributed to the students' mental resilience. These findings support the hypothesis that martial arts training, specifically Shorinji Kempo, plays a significant role in fostering resilience, helping students navigate challenges both in and outside the training environment.